Trial penalties under Florida’s sentencing guidelines: the moderating role of case seriousness - Lehmann, Peter S. (Crime & delinquency, 2021)
An extensive body of research has revealed that criminal defendants who are convicted at trials are given harsher sentences than those who plead guilty. However, it remains unclear how legally relevant case characteristics might moderate this relationship. In Florida, each felony offender is assigned a comprehensive numerical score which simultaneously quantifies multiple aspects of the seriousness of the case at hand, and judges evaluate this score in reference to the prescribed sentencing guideline recommendations. Analyses of data on defendants sentenced under this system (N = 690,565) reveal that, for sentences to prison, trial-plea disparities are greatest in the middle range of case seriousness. For prison sentence length, however, these differences are most amplified among the most serious cases.